Patterns for e-commerce applications - Rossi, Gustavo Héctor; Schwabe, Daniel; Lyardet, Fernando Daniel (2000)
In this paper we present some patterns we found in E-commerce applications. First, we briefly characterize these applications as a particular case of Web applications. We next review some Web patterns that can be used in E-commerce applications. Finally, we present five new patterns: Opportunistic Linking, Advising, Explicit Process, Easy Undo and Push Communication.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 13/03/2009)
EuroPLoP༼, IEEE Computer Society Press, 2000.
Keywords: DESARROLLO DE APLICACIONES WEB; PATRONES DE DISEÑO; COMERCIO ELECTRÓNICO